2015
DOI: 10.1007/s12288-015-0593-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Specificity and Titration of Red Cell Alloantibodies in Multiparous Antenatal Females at a Tertiary Care Centre from North India

Abstract: Screening and detection of clinically significant antibodies among antenatal women plays an important role in transfusion safety and preventing hemolytic disease of fetus and newborn. Routine screening of antenatal women for antibodies is not done in all blood centres of our country and so immunization rates are not known in pregnant women. We studied the prevalence of alloantibodies and titration of Anti D among antenatal multiparous women in Jammu region. In present prospective study, 750 antenatal multiparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
4
14
0
1
Order By: Relevance
“…Based on the fact that anti-D accounted for 64.10% of all alloantibodies, we need to focus more on anti-D immunoprophylaxis. In the present study, there was a glaring, statistically significant difference between alloimmunization rates in RhD-negative versus Rh D-positive group comparable with another study from North India showing statistical significance[ 26 ] (odds ratio = 0.0162, χ 2 = 138.47, P < 0.001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on the fact that anti-D accounted for 64.10% of all alloantibodies, we need to focus more on anti-D immunoprophylaxis. In the present study, there was a glaring, statistically significant difference between alloimmunization rates in RhD-negative versus Rh D-positive group comparable with another study from North India showing statistical significance[ 26 ] (odds ratio = 0.0162, χ 2 = 138.47, P < 0.001).…”
Section: Discussionsupporting
confidence: 87%
“…Koelewijn et al . [ 20 ] found that the prevalence of alloantibodies other than anti-D is 0.38% whereas that with another study carried out from North India was about 0.45%;[ 26 ] another study from South India showed prevalence of about 1.48. [ 27 ] Lurie et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent African studies showed somewhat lower D antibody prevalences of 4% to 6%, than in our Suriname women from African descent, possibly explained by study cohort differences (including D+, nonpregnant, and more primigravid women) and the use of other—less sensitive—antibody screenings techniques . D antibodies in four Indian studies in D– women varied between 2.5% and 21%, depending on whether anti‐D prophylaxis was applied and the use of a more D antibody–sensitive, enzyme‐modified antibody screening test …”
Section: Discussionmentioning
confidence: 60%
“…We found a statistically significant correlation between the development of antibody versus gravid status of pregnant women, APH, and past history of neonatal jaundice. Similar results were shown by Pahuja et al .,[ 3 ] Al-Joudi et al .,[ 22 ] and Sidhu et al .,[ 23 ] which shows increase in alloimmunization with increasing gravida status.…”
Section: Discussionmentioning
confidence: 99%